Differential Diagnostic Value of Histology in MPLC and IPM: A Systematic Review and Meta-Analysis - Tian, Sen; Li, Fuqi; Pu, Jin; Zheng, Yi; Shi, Hui; Dong, Yuchao; Chen, Ruohua; Bai, Chong (Frontiers in Oncology, 2022)
Background: The paramount issue regarding multiple lung cancer (MLC) is whether it represents multiple primary lung cancer (MPLC) or intrapulmonary metastasis (IPM), as this directly affects both accurate staging and subsequent clinical management. As a classic method, histology has been widely utilized in clinical practice. However, studies examining the clinical value of it in MLC have yielded inconsistent results, and thus remain to be evaluated. Here, we performed a meta-analysis to assess the differential diagnostic value of histology in MPLC and IPM, and to provide evidence-based medical evidence for clinical work. Methods: PubMed, EMBASE, and Web of Science databases were searched to collect relevant literature according to PRISMA. And inclusion and exclusion criteria were set up to screen and assess the literature. The data required for reconstructing a 2×2 contingency table were extracted directly or calculated indirectly from the included studies, and statistical analysis was carried out by using Stata15, Meta-DiSc 1.4, and Review Manager 5.4 software. Results: A total of 34 studies including 1075 pairs of tumors were included in this meta-analysis. Among which, 11 studies were about M-M standard, the pooled sensitivity and specificity were 0.78 (95%CI: 0.71-0.84) and 0.47 (95%CI: 0.38-0.55), respectively; 20 studies were about CHA, the pooled sensitivity and specificity were 0.76 (95%CI: 0.72-0.80) and 0.74 (95%CI: 0.68-0.79), respectively; 3 studies were about "CHA & Lepidic" criteria, the pooled sensitivity and specificity were 0.96 (95%CI: 0.85-0.99) and 0.47 (95%CI: 0.21-0.73), respectively. The combined pooled sensitivity, specificity, PLR, NLR, DOR, and the area under the SROC curve of 34 studies were 0.80 (95%CI: 0.73-0.86), 0.64 (95%CI: 0.51-0.76), 2.25 (95%CI: 1.59-3.17), 0.31 (95%CI: 0.23-0.43), 7.22 (95%CI: 4.06-12.81), and 0.81 (95%CI: 0.77-0.84), respectively. Conclusion: The current evidence indicated that histology had moderate differential diagnostic value between MPLC and IPM. Among 3 subgroups, "CHA & Lepidic" criteria showed the highest sensitivity and CHA showed the highest specificity. Further research is necessary to validate these findings and to improve the clinical credibility.